Quantifying shedding of synthetic fibers from textiles; a source of microplastics released into the environment - Carney Almroth, Bethanie M.; Åström, Linn; Roslund, Sofia; Petersson, Hanna; Johansson, Mats; Persson, Nils-Krister (Environmental science and pollution research international, 2018)
Microplastics in the environment are a subject of intense research as they pose a potential threat to marine organisms. Plastic fibers from textiles have been indicated as a major source of this type of contaminant, entering the oceans via wastewater and diverse non-point sources. Their presence is also documented in terrestrial samples. In this study, the amount of microfibers shedding from synthetic textiles was measured for three materials (acrylic, nylon, polyester), knit using different gauges and techniques. All textiles were found to shed, but polyester fleece fabrics shed the greatest amounts, averaging 7360 fibers/m −2 /L −1 in one wash, compared with polyester fabrics which shed 87 fibers/m −2 /L −1 . We found that loose textile constructions shed more, as did worn fabrics, and high twist yarns are to be preferred for shed reduction. Since fiber from clothing is a potentially important source of microplastics, we suggest that smarter textile construction, prewashing and vacuum exhaustion at production sites, and use of more efficient filters in household washing machines could help mitigate this problem.